Diagnosis of Bacteria Atypical Pneumonia Causative Agents by Using Indirect Immune Fluorescent Assay - Obaid , Samer Raheem (Jour Med Resh and Health Sci, 2022)
Pneumonia causes significant morbidity and mortality in children worldwide, especially in resource-poor settings.